Palatomaxillary Obturation and Facial Prosthetics in Head and Neck Reconstruction - Wang, Weitao; Shokri, Tom; Vincent, Aurora; Vest, Allison; Williams, Fayette; Ducic, Yadranko (Facial Plastic Surgery, 2020)
Rehabilitation of head and neck defects following trauma, oncologic resection, or congenital malformation is a challenging task. Not only is the restoration of three-dimensional form necessary for acceptable cosmesis, but simultaneous restoration of functional speech and swallow is also essential for optimal reconstruction outcomes. While advances in free tissue transfer have allowed surgical reconstruction of head and neck defects once considered inoperable and associated with poor quality of life, not all patients are ideal surgical candidates. As such, nonsurgical solutions to both functional and cosmetic restoration remain a necessary alternative option. Facial prostheses and palatomaxillary obturators have evolved with increasingly biocompatible materials as well as retention systems to address significant defects that challenge the limits of surgical reconstruction.
Keywords: prosthetic; palatal obturation; facial reconstruction